Effects of Selective Serotonin Reuptake Inhibitors on Interregional Relation of Serotonin Transporter Availability in Major Depression - James, Gregory M.; Baldinger-Melich, Pia; Philippe, Cecile; Kranz, Georg S.; Vanicek, Thomas; Hahn, Andreas; Gryglewski, Gregor; Hienert, Marius; Spies, Marie; Traub-Weidinger, Tatjana; Mitterhauser, Markus; Wadsak, Wolfgang; et al. (Frontiers in Human Neuroscience, 2017)
Selective serotonin reuptake inhibitors (SSRIs) modulate serotonergic neurotransmission by blocking reuptake of serotonin from the extracellular space. Up to now, it has been unclear how SSRIs achieve their antidepressant effect. However, task-based and resting state functional MRI studies, have demonstrated connectivity changes between brain regions. Here, we use positron emission tomography (PET) to quantify SSRI’s main target, the serotonin transporter (SERT), and assess treatment-induced molecular changes in the interregional relation of SERT binding potential (BPND). Nineteen out-patients with major depressive disorder (MDD) and 19 healthy controls (HC) were included in this study. Patients underwent three PET measurements with the radioligand [11C]DASB: (1) at baseline, (2) after a first SSRI dose and (3) following at least three weeks of daily intake. Controls were measured once with PET. Correlation analyses were restricted to brain regions repeatedly implicated in MDD pathophysiology. After three weeks of daily SSRI administration a significant increase in correlations of SERT BPND between several regions including midbrain, hippocampus, insula, anterior cingulate cortex and pallidum (p<0.05; FDR corrected) was revealed. No significant differences were found when comparing MDD patients and HC at baseline. These findings are in line with the clinical observation that treatment response to SSRIs is often achieved only after a latency of several weeks. The elevated associations in interregional SERT associations may be more closely connected to clinical outcomes than regional SERT occupancy measures and could reflect a change in the regional interaction of serotonergic neurotransmission during antidepressant treatment.